DETERMINATION OF FACTORS AND CONCEPTUAL FOUNDATIONS OF SUPPLY CHAIN FUNCTIONING RESILIENCE - Kirill V. Erygin (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
This article gives the key points description and results interpretation concerning the performed based on a combined approach study of factors and conceptual foundations of supply chain functioning resilience in understanding context of both practical and research communities. Experts from different organizations and countries were attracted to participate in the study. It gave the opportunity to consider wider variety of attitudes and estimations regarding the spotlighted issues. Basing on the empirical evidence obtained with the help of the combined approach as well as analysis of domestic and foreign scientific publications all four suggested hypotheses connected with the resilience in the sphere of logistics and supply chain management were tested, that ensured the theoretical increment in this area. Along with that the article proves the necessity and introduces the definition of supply chain functioning resilience. Additionally, the group of supply chain resilience factors and its relevant conceptual foundations are identified. The points provided in this article are focused on building theoretical bases of supply chain functioning resilience management. They can also be used in business for a deeper understanding of resilience problems nature in the sphere of logistics.